Growth mode control for direct-gap core/shell Ge/GeSn nanowire light emission. (November 2020) - Meng, Andrew C.; Braun, Michael R.; Wang, Yanming; Peng, Siying; Tan, Wanliang; Lentz, J. Zach; Xue, Muyu; Pakzad, Anahita; Marshall, Ann F.; Harris, James S.; Cai, Wei; McIntyre, Paul C.
Graphical abstract: Abstract: Germanium-tin is a promising semiconductor alloy system for novel light emitting devices and optical sensors in the mid-IR region. For sufficiently high Sn compositions, the material has a direct band-gap near 0.5 eV, and could have applications either as a detector or an emitter. Although high Sn compositions have been achieved in Ge1− x Sn x through a variety of growth strategies, the understanding of how chemical vapor deposition conditions affect Sn composition and optical properties in core–shell Ge/Ge1− x Sn x nanowires is still lacking. In this study, gas precursor partial pressures and shell growth temperatures are systematically varied to provide guiding principles to overcome obstacles for higher Sn incorporation. We achieve a direct band-gap material using an elastically compliant Ge core nanowire substrate. In the course of the growth study, we demonstrate several findings regarding the Ge1− x Sn x shell growth mechanism. First, we observe an H2 passivation effect in which higher H2 to SnCl4 partial pressure ratio results in a concurrent increase in axial wire growth and decrease in radial growth. Second, we find that Ge1− x Sn x shell growth in the studied CVD process is mass transport limited. Third, our results suggest that low shell growth temperature and high shell growth rate facilitate high Sn composition through metastable Sn solute trapping due to suppressed surface diffusion relative to the velocity of advancing shell surface steps. In this work, we demonstrate single nanowire photoluminescence at room temperature from core-shell Ge/Ge0.88 Sn0.12 nanowires. Understanding the Ge1− x Sn x shell growth mechanism via chemical vapor deposition (CVD) facilitates achieving minimal residual strain in the shell and the high crystalline quality and large Sn composition necessary for the observed optical properties. The results are universally applicable to Ge1− x Sn x thin film epitaxy on compliant substrates including grown or etched nanowires, nanosheets, or free-standing 2D crystals.